Trabalho individual e trabalho coletivo de pequenos produtores rurais: um estudo na cooperselene de Sinop (MT) - Peiter, Mara Beatriz (2011)
The current literature about the modalities of organizations that deal with the solidarity economy tends to affirm an alternative attitude of the new solidarity experiences of the selfmanagement and cooperation given the opening that fall into the capitalist relations of production. In Brazil, the culture of cooperation is observed since the era of Portuguese colonization. This process emerged in the Brazilian Cooperative Movement came out of in the late 19th century, incited by civil servants, militaries, personnel professionals and workers, to serve their needs. They would represent the manifestation of a new method of the work organization and economic activities in general. The city of Sinop/MT where this research was carried out, today focuses a large volume of business related to the husbandry and each day more is growing according to increase of the population. There are many cattlemen who assure the economics of the agribusiness in the town. Then, we formulate the question about how occurred the trajectory of the milk producer in the municipality, whose this, is inserted into an organization that before was associative and now is converted into a cooperative, in search of better production and commercialization. This, the work intended to discuss this topic showing data from an exploratory qualitative research carried out in the Cooperativa Agrícola Selene Cooperselene-located in the rural area on Selene Road, town of Sinop/MT in the period of October, 2010 to March, 2011. In the results of this research we see the strengthening of security of the milk producer with to the delivery and sale of his product in the entrepreneurial organization. The data shows that labor relations have improved when cooperative members departed from the individual to the collective work, as well as growth prospects and insertion of the new products which are part of the internal politics of the group. Despite of all the advances, we realized that there are lot of things to be still done with regard to work about cooperativism and associativism. The complex access to availability of financial resources and subsidies of the government still is present and is the cause for complaint of current cooperative members. However it is known that the process is gradual, but can be achieved always seeking the strengthening and improvements to the collective in this model of organization.